Implementation of E-Filing, Tax Compliance Costs and Social Environment on Taxpayer Compliance - Silviyani, Silviyani; Margie, Lyandra Aisyah (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to analyze the implementation of e-filing, tax compliance costs, and the social environment on taxpayer compliance. This type of research is quantitative research with primary data sources by distributing questionnaires. The population in this study are taxpayers registered at the Pratama Serpong Tax Service Office (KPP). In this research, the sampling technique was carried out using the convenience sampling method with the number of samples obtained being 100 respondents. The data analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression testing and hypothesis testing. Based on the test results, the results obtained are that the implementation of e-filing (Χ1), tax compliance costs (Χ2) and the social environment (Χ3) simultaneously have a significant effect on taxpayer compliance. Meanwhile, partially, the implementation of e-filing (Χ1) and the social environment (Χ3) have an effect on taxpayer compliance, while tax compliance costs (Χ2) partially have no and significant effect on taxpayer compliance at the Pratama Serpong Tax Service Office (KPP).